Aromatherapy blended lemon and lavender has an effect on nausea and vomiting in first trimester pregnant women at PMB Entin Hartini - Aisya, Nabila Shafa; Meiranny, Arum; Arisanti, Atika Zahria; Hudaya, Isna (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2024)
Introduction: Nausea and vomiting are common complaints in the first trimester of pregnancy. One treatment to reduce nausea and vomiting is non-pharmacological therapy by providing a mixture of lemon and lavender aromatherapy. In this study, there was only one group, namely the intervention group, which received blended lemon and lavender aromatherapy. Before carrying out the intervention, pregnant women in the first trimester are given a pre-test to find out how often pregnant women feel nauseous and vomit. Then the pregnant mother is taught how to use aromatherapy blended lemon and Lavender with Roll On which will be done in the morning and evening for 6 consecutive days. -continuously. Next, another post-test was carried out to determine the effectiveness of providing aromatherapy.Objectives: The aim of this study was to determine the effectiveness of giving a mixture of lemon and lavender aromatherapy against nausea and vomiting in first trimester pregnant women at PMB (Independent Midwife Practice) Entin Hartini, A.Md. Keb Mrebet District, Purbalingga Regency.Methods: The type of research used in this research is pre-experimental with a One Group Pre-Test and Post-Test design.Results: The Wilcoxon test results were obtained by Asymp. signature. 0.00 that there is an effect of giving a mixture of lemon and lavender aromatherapy in reducing nausea and vomiting (?- value = 0.00).Conclusions: There is effectiveness of giving a mixture of lemon and lavender aromatherapy for nausea and vomiting in first trimester pregnant women at PMB Entin Hartini, A.Md.Keb.